Hyperoxidation of Peroxiredoxin 6 Induces Alteration from Dimeric to Oligomeric State - Sharifun Shahnaj; Rimpy Kaur Chowhan; Potshangbam Angamba Meetei; Pushpa Kakchingtabam; Khundrakpam Herojit Singh; Laishram Rajendrakumar Singh; Potshangbam Nongdam; Aron B. Fisher; Hamidur Rahaman (MDPI AG, 2019)
Peroxiredoxins(Prdx), the family of non-selenium glutathione peroxidases, are important antioxidant enzymes that defend our system from the toxic reactive oxygen species (ROS). They are thiol-based peroxidases that utilize self-oxidation of their peroxidatic cysteine (Cp) group to reduce peroxides and peroxidized biomolecules. However, because of its high affinity for hydrogen peroxide this peroxidatic cysteine moiety is extremely susceptible to hyperoxidation, forming peroxidase inactive sulfinic acid (Cys-SO2H) and sulfonic acid (Cys-SO3H) derivatives. With the exception of peroxiredoxin 6 (Prdx6), hyperoxidized sulfinic forms of Prdx can be reversed to restore peroxidase activity by the ATP-dependent enzyme sulfiredoxin. Interestingly, hyperoxidized Prdx6 protein seems to have physiological significance as hyperoxidation has been reported to dramatically upregulate its calcium independent phospholipase A2 activity. Using biochemical studies and molecular dynamic (MD) simulation, we investigated the roles of thermodynamic, structural and internal flexibility of Prdx6 to comprehend the structural alteration of the protein in the oxidized state. We observed the loosening of the hydrophobic core of the enzyme in its secondary and tertiary structures. These changes do not affect the internal dynamics of the protein (as indicated by root-mean-square deviation, RMSD and root mean square fluctuation, RMSF plots). Native-PAGE and dynamic light scattering experiments revealed the formation of higher oligomers of Prdx6 under hyperoxidation. Our study demonstrates that post translational modification (like hyperoxidation) in Prdx6 can result in major alterations of its multimeric status.